Pathways between neighbourhood factors, stress and glycaemic control in individuals with type 2 diabetes in Southeastern United States: a cross-sectional pathway analysis. Issue 10 (25th October 2022) - Mosley-Johnson, Elise; Walker, Rebekah; Hawks, Laura; Walker, Shannon L; Mendez, Carlos; Campbell, Jennifer A; Egede, Leonard E
Abstract : Objectives: Understanding the pathway by which neighbourhood factors influence glycaemic control may be crucial to addressing health disparities in diabetes. This study aimed to examine if the pathway between neighbourhood factors and glycaemic control is mediated by stress. Design: Structured equation modelling (SEM) was used to investigate direct and indirect effects in the relationship between neighbourhood factors, stress and glycaemic control, with standardised estimates to allow comparison of paths. Participants: Data was obtained from 615 adults with type 2 diabetes in the Southeastern United States. Primary and secondary outcome measures: The primary outcome variable was glycaemic control determined by glycated haemoglobin (HbA1c) within the prior 6 months. Neighbourhood factors included neighbourhood violence, aesthetic quality of the neighbourhood, access to healthy food, and social cohesion. Stress was measured using the perceived stress scale. Results: In the final model (χ 2 (158)=406.97, p<0.001, root mean square error of approximation=0.05, p-close 0.38, Comparative Fit Index=0.97, Tucker-Lewis index=0.96, the coefficient of determination=1.0), violence (r=0.79, p=0.006), neighbourhood aesthetics (r=0.74, p=0.02) and social cohesion (r=0.57, p=0.04) were significantly associated with higher perceived stress. Stress (r=0.06, p=0.004) was directly associated with higher glycaemic control. Significant indirect effects existed between violence and higher HbA1c (r=0.05, p=0.04). After controlling for other neighbourhood factors, there was no significant relationship between access to healthy food and either stress or glycaemic control. Conclusions: While a number of neighbourhood factors were directly associated with stress, only neighbourhood violence had a significant indirect effect on glycaemic control via stress within the tested pathway. Future studies should examine individual-level stress management interventions and should consider community-level interventions targeting neighbourhood violence as strategies for addressing disparities in diabetes.